Dos referentes para la Filosofía en Iberoamérica en el siglo XXI: Alberto Wagner de Reyna y Víctor Andrés Belaunde - González Umeres, Luz (Mercurio Peruano, 2013)
In this work – in the frame of the International Interdisciplinary Congress of Philosophy related to Believes, its validity and its sense in the XXI century- two Ibero-American thinkers and skillful experts of the international life and its tendencies are introduced. One, who passed away less than a lustrum in the city of Paris in France, known in Cordova and appreciated among his Argentinean friends, - Alberto Wagner de Reyna-. And another man of thought and international trajectory, born at the edge of the XIX and XX century and founder of a prestigious Humanities magazine- Mercurio Peruano in 1918, which was famous in Peru in the XX century- called Victor Andrés Belaunde, who passed way in New York in 1996, leading the delegation of Peru in the General Assembly of the United Nations.
Keywords: Alberto Wagner de Reyna, Víctor Andrés Belaunde, Christianity, Peruvian philosophy.